2013
DOI: 10.2527/jas.2011-5014
|View full text |Cite
|
Sign up to set email alerts
|

Stress susceptibility in pigs supplemented with ractopamine1

Abstract: Ractopamine is a β-adrenergic agonist used as an energy repartitioning agent in the diets of finishing pigs. Most ractopamine studies are limited to evaluations of growth performance and meat quality, and there is little information on the effects of this additive on the behavior and welfare of pigs. Therefore, the objective of this study was to evaluate various indicators of stress caused by feeding diets containing ractopamine. One hundred seventy barrows and 170 gilts weighing 107.3 kg were allocated to 30 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 29 publications
1
9
3
Order By: Relevance
“…However, the effects of RAC on fighting may have been minor as this did not result in greater carcass damage scores at the plant. The results of Rocha et al (2013) align with a previous study that reported no effects of RAC on skin/carcass lesions ( Athayde et al, 2013 ). Lastly, other studies designed to measure the impact of RAC on general behaviors reported minimal RAC effects on agonistic behaviors ( Schaefer et al, 1992 ; Marchant-Forde et al, 2003 ).…”
Section: Resultssupporting
confidence: 87%
See 3 more Smart Citations
“…However, the effects of RAC on fighting may have been minor as this did not result in greater carcass damage scores at the plant. The results of Rocha et al (2013) align with a previous study that reported no effects of RAC on skin/carcass lesions ( Athayde et al, 2013 ). Lastly, other studies designed to measure the impact of RAC on general behaviors reported minimal RAC effects on agonistic behaviors ( Schaefer et al, 1992 ; Marchant-Forde et al, 2003 ).…”
Section: Resultssupporting
confidence: 87%
“…The RAC effects on cortisol concentrations during baseline, post-handling, post-transport, and exsanguination are summarized in Table 15 . These studies indicate that RAC had no effect on baseline cortisol values at 5 and 7.5 mg/kg ( Peterson et al, 2015 ), 10 mg/kg ( Marchant-Forde et al, 2003 ), or 20 mg/kg ( James et al, 2013 ; Study #1) for feeding durations of 28 d. Likewise, 3 studies reported no effects of feeding 5 mg/kg ( Athayde et al, 2013 ), 7.5 mg/kg ( Rocha et al, 2013 ), or 10 mg/kg ( Marchant-Forde et al, 2003 ; Athayde et al, 2013 ) on either plasma or urinary cortisol values measured at post-transportation or exsanguination. The effects of RAC on post-handling cortisol values are inconsistent in the literature.…”
Section: Resultsmentioning
confidence: 86%
See 2 more Smart Citations
“…Therefore, the results of this study indicated that ractopamine can act as a stressor agent culminating in the activation of the hypothalamic-pituitary-interrenal-axis in pacu when the feed is supplemented with β-adrenergic in concentrations higher than 11.25 mg kg −1 and is provided to animals in the finishing phase during 60 days. Similarly, increased circulating cortisol levels were not noted in finishing pigs fed diets containing 10 mg kg −1 or less of ractopamine (Athayde et al, 2013). There are no scientific reports that explain how and why chronic exposure to high concentrations of dietary ractopamine is recognized by the hypothalamus of teleost fish as a stressor agent and, therefore, this warrants further investigation.…”
Section: Discussionmentioning
confidence: 94%